Metabolic engineering of Synechococcus elongatus PCC 7942 for improvement of 1, 3-propanediol and glycerol production based on in silico simulation of metabolic flux distribution. Issue 1 (December 2017) - Hirokawa, Yasutaka; Matsuo, Shingo; Hamada, Hiroyuki; Matsuda, Fumio; Hanai, Taizo
Abstract Background Production directly from carbon dioxide by engineered cyanobacteria is one of the promising technologies for sustainable future. Previously, we have successfully achieved 1, 3-propanediol (1, 3-PDO) production usingSynechococcus elongatus PCC 7942 with a synthetic metabolic pathway. The strain into which the synthetic metabolic pathway was introduced produced 3.48 mM (0.265 g/L) 1, 3-PDO and 14.3 mM (1.32 g/L) glycerol during 20 days of incubation. In this study, the productivities of 1, 3-PDO were improved by gene disruption selected by screening with in silico simulation. Methods First, a stoichiometric metabolic model was applied to prediction of cellular metabolic flux distribution in a 1, 3-PDO-producing strain ofS. elongatus PCC 7942. A genome-scale model ofS. elongatus PCC 7942 constructed by Knoop was modified by the addition of a synthetic metabolic pathway for 1, 3-PDO production. Next, the metabolic flux distribution predicted by metabolic flux balance analysis (FBA) was used for in silico simulation of gene disruption. As a result of gene disruption simulation, NADPH dehydrogenase 1 (NDH-1) complexes were found by screening to be the most promising candidates for disruption to improve 1, 3-PDO production. The effect of disruption of the gene encoding a subunit of the NDH-1 complex was evaluated in the 1, 3-PDO-producing strain. Results and Conclusions During 20 days of incubation, thendhF1 -null 1, 3-PDO-producing strain showed the highest titers: 4.44 mM (0.338 g/L) 1, 3-PDO and 30.3 mM (2.79 g/L) glycerol. In this study, we successfully improved 1, 3-PDO productivity on the basis of in silico simulation of gene disruption.